Behind The Positive Attitude of The Indonesian Army Academic Staff: A Rasch Model Analysis - Didin Zainal Abidin; Wibowo Wibowo; I Ketut R. Sudiarditha; Maria Grace Herlina (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
The Indonesian National Army is an integral part of the Indonesia Archipelago. As the national component, the Army has the main task of maintaining the country's sovereignty and territorial integrity of the unitary state. Therefore it needs high-quality human resources. The aim of the research was examining the real motivational factors behind the positive attitude of The Indonesian Army Academic Staff. The study applied a Rasch Model method. The Rasch Model Analysis was used to examine the research variable based on its dimensions and indicators. The research results show that team-building development process has been successfully proven, based on the research results. The Rasch Model analysis also shows that team-spirit among The Indonesian National Army members is very solid. It is the most satisfactory factor that creates positive task-attitude among the army academic staff. At the same time, the promotion is the most challenging factor to agree with among them.